2022
DOI: 10.3390/cancers14061553
|View full text |Cite
|
Sign up to set email alerts
|

High Expression of Casein Kinase 2 Alpha Is Responsible for Enhanced Phosphorylation of DNA Mismatch Repair Protein MLH1 and Increased Tumor Mutation Rates in Colorectal Cancer

Abstract: DNA mismatch repair (MMR) deficiency plays an essential role in the development of colorectal cancer (CRC). We recently demonstrated in vitro that the serine/threonine casein kinase 2 alpha (CK2α) causes phosphorylation of the MMR protein MLH1 at position serine 477, which significantly inhibits the MMR. In the present study, CK2α-dependent MLH1 phosphorylation was analyzed in vivo. Using a cohort of 165 patients, we identified 88 CRCs showing significantly increased nuclear/cytoplasmic CK2α expression, 28 tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Furthermore, we were able to verify the importance of CK2α-mediated MLH1 phosphorylation in vivo [ 496 ]. In a cohort of 165 CRC patients, we could show that enhanced MLH1 phosphorylation was significantly associated with high nuclear/cytoplasmic CK2α expression.…”
Section: Importance Of Ck2 In Different Hallmarks Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we were able to verify the importance of CK2α-mediated MLH1 phosphorylation in vivo [ 496 ]. In a cohort of 165 CRC patients, we could show that enhanced MLH1 phosphorylation was significantly associated with high nuclear/cytoplasmic CK2α expression.…”
Section: Importance Of Ck2 In Different Hallmarks Of Cancermentioning
confidence: 99%
“…In addition, high nuclear/cytoplasmic CK2α levels could be significantly correlated with a reduced 5-year survival outcome of patients. Furthermore, we detected enriched somatic mutation rates in tumors with high nuclear/cytoplasmic CK2α expression and speculated that enriched somatic mutation rates are induced by the reduction of MMR, caused by CK2-mediated phosphorylation of MLH1 [ 496 ]. Recently, MMR deficiency and high rates of microsatellite instability have been shown to be predictive of anti-programmed cell death 1 (PD-1)/PD-L1 immunotherapy efficacy.…”
Section: Importance Of Ck2 In Different Hallmarks Of Cancermentioning
confidence: 99%
“…Notably, nearly 3% of CRC is classified as MSS with high TMB. These MSS patients with high TMB may respond favourably to ICI‐based therapy 120 . The underlying mechanism for the generation of high TMB in MSS CRC is still not clear.…”
Section: The Neoantigen‐based Therapy In Crcmentioning
confidence: 99%
“…These MSS patients with high TMB may respond favourably to ICI-based therapy. 120 The underlying mechanism for the generation of high TMB in MSS CRC is still not clear. Neoantigen-derived epitopes (neoepitopes) on HLA-I have also been observed in MSS CRC.…”
Section: The Prognostic Role Of Neoantigens In Crcmentioning
confidence: 99%
“…We previously showed that MLH1 can be phosphorylated by casein kinase 2 α (CK2α) at amino acid position serine 477 (S477) and we identified that phosphorylation of MLH1 at position S477 can switch off MMR activity in vitro 14 . Very recently, we were able to demonstrate in vivo, that CK2α is frequently overexpressed in CRCs and that a high nuclear/cytoplasmic expression of CK2α is responsible for enhanced phosphorylation of MLH1 and increased tumor mutation rates in these tumors 15 . Moreover, affected patients demonstrated a significantly reduced 5-year survival outcome 15 .…”
Section: Introductionmentioning
confidence: 99%